A Review of Salinity's Impact on Relevant Aquatic Drug Approval Technical Sections. Issue 3 (27th September 2022) - Ramee, Shane
Abstract: Currently, in the USA, there are no aquatic animal drugs approved for use in saltwater‐reared finfish. As U.S. aquaculture expands into the marine environment, it is imperative to maximize the current knowledge base to make new approvals for saltwater use as efficient as possible. This article reviews literature relevant to how the saltwater environment may affect the Effectiveness, Target Animal Safety, and Human Food Safety major technical sections of a new animal drug approval. Though research on this subject is limited, there are pharmacokinetic and toxicological studies that have utilized euryhaline species to isolate salinity as the independent variable. I summarize these studies to demonstrate patterns that could facilitate more effective and efficient transfer of data previously used for freshwater drug approvals to be used for potential saltwater approvals. Research suggests that drug residue clearance rates are generally faster or at least similar in salt water if other factors are held constant, suggesting that consistent or shorter withdrawal times may be appropriate for saltwater application. However, faster clearance rates may cause a reduction in efficacy in some cases. The effects of salt water on drug toxicity are much less clear, are possibly highly compound dependent, and deserve further research. This suggests that any future drug approvals for saltwater use should begin by identifying the appropriate effective dose in salt water before addressing the other technical sections.